2013
DOI: 10.1002/ppul.22751
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia: Clinical grading in relation to ventilation/perfusion mismatch measured by single photon emission computed tomography

Abstract: Bronchopulmonary dysplasia (BPD) is a significant cause of morbidity in the preterm population. Clinical severity grading based on the need for supplemental oxygen and/or need for positive airway pressure at 36 weeks postmenstrual age does not yield reproducible predictive values for later pulmonary morbidity. Single photon emission computed tomography (SPECT) was used to measure the distribution of lung ventilation (V) and perfusion (Q) in 30 BPD preterm infants at a median age of 37 weeks postmenstrual age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…It is characterized by alveolar growth inhibition resulting in a reduced alveolar surface area. We have previously shown that at 36 weeks’ postconceptional age, most of the infants with BPD had abnormalities in ventilation/perfusion (V/Q) matching . Recent evidence indicates that alveolar size and number increase during childhood and young adulthood, suggesting a potential for pulmonary recovery after the neonatal period in survivors with BPD .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by alveolar growth inhibition resulting in a reduced alveolar surface area. We have previously shown that at 36 weeks’ postconceptional age, most of the infants with BPD had abnormalities in ventilation/perfusion (V/Q) matching . Recent evidence indicates that alveolar size and number increase during childhood and young adulthood, suggesting a potential for pulmonary recovery after the neonatal period in survivors with BPD .…”
Section: Introductionmentioning
confidence: 99%
“…They also assessed the effects of inhaled anesthetic administration on these distributions during spontaneous breathing [12]. More recently, similar methods have been applied to assess bronchopulmonary dysplasia [13] and in a mouse model of cigarette exposure [14].…”
Section: Imaging Methods For Ventilation/ Perfusion Distributionsmentioning
confidence: 99%
“…35,36 Fig. 4 is an example of a ventilation scan demonstrating uneven radiotracer distribution in the lungs of a 6-month-old BPD survivor.…”
Section: Nuclear Medicinementioning
confidence: 98%